2011
DOI: 10.4028/www.scientific.net/amm.147.70
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genetic Programming for Estimation of Soil Compaction Parameters

Abstract: The aim of this study is to propose two numerical models by a well-known soft computing method, Genetic Programming (GP), for the estimation of soils compaction parameters. Genetic Programming is a pattern recognition approach that has the ability of modeling the non-linear behavior of complex engineering problems. The input variables were the soil classification properties, and the outputs were the Optimum Moisture Content (OMC) and Maximum Dry Density (MDD). To provide model, a database including properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
7
5
0
Order By: Relevance
“…Then, the values of γ dmax will decrease upon an increment of clay content. These results are in line with the outcomes of the investigations conducted by [2,3,[7][8][9][12][13][14] which revealed that the γ dmax decreases when the LL increases. Moreover, the results corroborate the studies performed by [5,6,9,10] that reported the reduction of the γ dmax upon the increment of the PI.…”
Section: Analysis Of the Correlations Between The Compaction Features (W Op γ Dmax ) And The Atterberg Limitssupporting
confidence: 89%
See 3 more Smart Citations
“…Then, the values of γ dmax will decrease upon an increment of clay content. These results are in line with the outcomes of the investigations conducted by [2,3,[7][8][9][12][13][14] which revealed that the γ dmax decreases when the LL increases. Moreover, the results corroborate the studies performed by [5,6,9,10] that reported the reduction of the γ dmax upon the increment of the PI.…”
Section: Analysis Of the Correlations Between The Compaction Features (W Op γ Dmax ) And The Atterberg Limitssupporting
confidence: 89%
“…Atterberg limits are good predictors of the γ dmax . However, the utilization of the specific gravity can improve the accuracy of the γ dmax value like previously proposed by [5][6][7]. A 3-dimensional representation of the correlation between the W OP , liquid limit and plasticity index is shown in Figure 2.…”
Section: Analysis Of the Correlations Between The Compaction Features (W Op γ Dmax ) And The Atterberg Limitsmentioning
confidence: 92%
See 2 more Smart Citations
“…Likewise, in reference [37], the authors predicted the performance characteristics of stabilized soils by utilizing a variant of genetic programming, namely, linear genetic programming (LGP), and a hybrid search algorithm coupling LGP and simulated annealing (SA), called LGP/SA. In their own efforts, Naderi et al [38] proposed two numerical models by employing GP for the estimation of soil compaction parameters. However, their input variables were the soil classification properties and the output variables were the optimum moisture content (OMC) and maximum dry density (MDD).…”
Section: Evolutionary Computation Techniques For Predicting Consistency Limit: Genetic Programming and Artificial Neuralmentioning
confidence: 99%